No-Touch Radiofrequency Ablation of VX2 Hepatic Tumors In Vivo in Rabbits: A Proof of Concept Study - Kim, Tae-Hyung (Korean J Radiol, 2018)
OBJECTIVE: In a proof of concept study, we compared no-touch radiofrequency ablation (NtRFA) in bipolar mode with conventional direct tumor puncture (DTP) in terms of local tumor control (LTC), peritoneal seeding, and tumorigenic factors, in the rabbit VX2 subcapsular hepatic tumor model. MATERIALS AND METHODS: Sixty-two rabbits with VX2 subcapsular hepatic tumors were divided into three groups according to the procedure: DTP-RFA (n = 25); NtRFA (n = 25); and control (n = 12). Each of the three groups was subdivided into two sets for pathologic analysis (n = 24) or computed tomography (CT) follow-up for 6 weeks after RFA (n = 38). Ultrasonography-guided DTP-RFA and NtRFA were performed nine days after tumor implantation. LTC was defined by either achievement of complete tumor necrosis on histopathology or absence of local tumor progression on follow-up CT and autopsy. Development of peritoneal seeding was also compared among the groups. Serum hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6) were measured via ELISA (Elabscience Biotechnology Co.) after RFA for tumorigenic factor evaluation. RESULTS: Regarding LTC, there was a trend in NtRFA (80%, 20/25) toward better ablation than in DTP-RFA (56%, 14/25) (p = 0.069). Complete tumor necrosis was achieved in 54.5% of DTP-RFA (6/11) and 90.9% of NtRFA (10/11). Peritoneal seeding was significantly more common in DTP-RFA (71.4%, 10/14) than in NtRFA (21.4%, 3/14) (p = 0.021) or control (0%). Elevations of HGF, VEGF or IL-6 were not detected in any group. CONCLUSION: No-touch radiofrequency ablation led to lower rates of peritoneal seeding and showed a tendency toward better LTC than DTP-RFA.